Disease recognition is related to specific autobiographical memory deficits in alcohol-dependence. Issue 2 (15th December 2015) - Poncin, Marie; Neumann, Aurore; Luminet, Olivier; Vande Weghe, Noémie; Philippot, Pierre; de Timary, Philippe
Abstract: The particularly high treatment gap in alcohol-dependence suggests the existence of important barriers to treatment decision and in particular difficulties in problem recognition. This study tested the relation between problem recognition and self-related memories. Forty-one recently detoxified alcohol-dependent individuals (AD) were compared to twenty alcoholic subjects that were abstinent for 6 months or more (recruited among alcoholics-anonymous (AA)), and to twenty controls on autobiographical memories elicited by pictures depicting or not alcohol using the autobiographical memory test. Autonoetic consciousness was measured with the Remember/Know paradigm. We tested whether memories performances were related with data obtained on the readiness to change questionnaire (RCQ) or with consciousness of the severity of drinking. AD subjects provided less specific memories than control and AA subjects, and fewer Remember responses than controls. The deficits in AD subjects were not specific for memories elicited by pictures depicting alcohol, suggesting a global deficit. Autobiographical memories specificity was negatively correlated to scores of consciousness of the severity of drinking but not to RCQ. Our results support potential recovery of autobiographical memory with abstinence. AD's deficits in autobiographical memory were related to capacities to recognize the severity and therefore may be a barrier to treatment decision. Highlights: A cognitive approach of disease recognition in alcohol-dependence. Deficits in autobiographic memory are linked to decreased consciousness of severity. Autobiographical memory is unrelated to readiness to change in alcohol dependence. Reduced access to memories is not specific to alcohol experiences. Potent recovery of autobiographical memory (and disease recognition) with abstinence.